The Research of Through-casing Resistivity Logging Logging Calibration System Leakage Current Measurement Method - ZHANG Jiatian; WANG Huanyou; BAO Dezhou (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper introduces the logging principle of through-casing resistivity logging technology, finds a phenomenon that the leakage current measurements are susceptible to sufferring interferences. The through-casing resistivity logging technology in Russia and that of Schlumberger are studied, and the system of through-casing resistivity logging is established to improve the accuracy of calibrating, testing and measuring of the instrument. In this paper, distribution parameters of the form is replaced by the lumped parameter, and precision resistor array simulation in formation leakage current and scale pool simulation in different resistivity of formation are conducted, which make the dynamic range of the simulation in formation resistivity of the medium increase to 1- 300 Ω·m and meet the requirement of through-casing resistivity logging technology measurement range, 1 Ω·m ~ 100 Ω·m. Since the measuring signals of calibration acquisition and processing systems are extremely weak and calculation signals need to tell the nV (nanovolts) level, the high accurate data acquisition system of 24 digits is applied. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3671